Anmeldelser - Mathiassen, Finn (Danish Yearbook of Musicology, 1981)
Review of: Finn Egeland Hansen: The Grammar of Gregorian Tonality. An Investigation Based on the Repertory in Codex H 159, Montpellier (=Studier og publikationer fra Musikvidenskabeligt Institut, Aarhus Universitet, III-IIIa). Dan Fog Musikforlag. København, 1979.